2017
DOI: 10.1038/tp.2017.96
|View full text |Cite
|
Sign up to set email alerts
|

Gray matter anomalies in pedophiles with and without a history of child sexual offending

Abstract: Pedophilia is a psychiatric disorder that is inter-related with but distinct from child sexual offending (CSO). Neural alterations reportedly contribute to both pedophilia and CSO, but until now, no study has distinguished the brain structural anomalies associated with pedophilia from those specifically associated with CSO in pedophilic men. Using high-resolution T1-weighted brain images and voxel-based morphometry, we analyzed the gray matter (GM) volume of the following 219 men recruited at four acquisition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 35 publications
(41 reference statements)
1
38
0
3
Order By: Relevance
“…Interestingly, the risk of re-offending [assessed with the SSPI-2, Screening Scale of Pedophilic Interest 2 nd version, (66)] was associated with lower local gray matter volume in the right dorsomedial prefrontal cortex/anterior cingulate cortex. This finding might be related to research results on deficient inhibitory control in offending pedophiles (see below) (64). In a large sample of 283 individuals, Lett et al could further demonstrate with moderate effect sizes that as compared to non-offending pedophiles (n = 77) and healthy controls (n = 133), pedophiles with child sexual offenses (n = 73) showed lower IQ-performance, reduced cortical thickness in the right motor cortex, reduced cortical surface area comprising bilateral frontal, temporal, cingulate, and insular regions, and reduced white matter fractal anisotropy particularly in the corpus callosum (65).…”
Section: Structural Imagingmentioning
confidence: 53%
See 2 more Smart Citations
“…Interestingly, the risk of re-offending [assessed with the SSPI-2, Screening Scale of Pedophilic Interest 2 nd version, (66)] was associated with lower local gray matter volume in the right dorsomedial prefrontal cortex/anterior cingulate cortex. This finding might be related to research results on deficient inhibitory control in offending pedophiles (see below) (64). In a large sample of 283 individuals, Lett et al could further demonstrate with moderate effect sizes that as compared to non-offending pedophiles (n = 77) and healthy controls (n = 133), pedophiles with child sexual offenses (n = 73) showed lower IQ-performance, reduced cortical thickness in the right motor cortex, reduced cortical surface area comprising bilateral frontal, temporal, cingulate, and insular regions, and reduced white matter fractal anisotropy particularly in the corpus callosum (65).…”
Section: Structural Imagingmentioning
confidence: 53%
“…Recent reviews and meta-analyses investigating differences between individuals sexually oriented toward children and individuals sexually oriented toward adults revealed that their brain structures are very similar in nature (17,62,63). As indicated by two recent studies, aberrant neuroanatomy might rather be associated with child sexual abuse than with pedophilia (64,65). Applying voxel based morphometry (VBM) in 219 individuals, Schiffer et al failed to find group differences in the relative gray matter volume specifically associated with pedophilia (64).…”
Section: Structural Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a differentiated approach must be taken into consideration of these results as they are exclusively related to pedophilic sex offenders. Abnormalities in the anterior cingulate cortex were previously linked to higher risk of re-offending in pedophilic child molesters ( Schiffer et al, 2017 ). Therefore, we speculate that dACC GABA deficit can only be found in pedophilic patients with a history of child sexual offending.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous findings showing some kind of mal-functioning mostly involved pedophiles that already committed child sex offending. By carefully comparing pedophiles with and without a history of child sex offenses recent studies revealed that mal-functioning is mostly restricted to those that committed child sex offenses ( Kargel et al, 2016 ; Massau et al, 2017b ; Schiffer et al, 2017 ). Accordingly, the neurobiological underpinnings of pedophilia remain unknown.…”
Section: Introductionmentioning
confidence: 99%